Improving Healthcare Outcomes with RF-enabled Health Information Systems - Ahmad Tasnim Siddiqui (International Journal of Radio Frequency Innovations, 2025)
Health Information Technology (HIT) plays a crucial role in improving healthcare by making medical data more accessible, accurate, and efficient. Using radio frequency (RF) technology, HIT enables the wireless sharing of important health information—like patient records, and treatments—between patients, doctors, and other healthcare providers. This helps reduce paperwork, cut costs, and improve the quality of care. By reducing the reliance on paper-based records, RF-based HIT helps streamline administrative processes, cut costs, and minimize the risk of human error. For example, electronic health records (EHRs) and personal health records (PHRs) make it easier for healthcare providers to access up-to-date patient information, leading to more accurate diagnoses and timely treatments. RF technology holds significant promise in healthcare, offering numerous benefits such as enhancing care quality, reducing costs, minimizing paperwork, and supporting more accurate diagnoses. It also plays a key role in improving safety by lowering the risk of medication errors and safeguarding sensitive patient data. Additionally, hospitals can use it to track and store patient information, aiding research and informed decision-making. With the advancements in health information technology, RF-enabled systems have brought greater focus to shared decision-making. As the American Medical Association (2012) explains, "shared decision-making is a process or tool that empowers both patients and doctors to collaborate in determining the best treatment approach based on medical evidence and the patient's care needs." RF technology also supports real-time communication, allowing medical teams to collaborate more effectively, even when they are in different locations. By integrating electronic health records (EHRs), personal health records (PHRs), and security measures, RF-based HIT ensures that sensitive information remains safe while supporting real-time decision-making and communication. This paper looks at how RF technology is transforming healthcare, the benefits it brings, and the challenges we still need to overcome to make it even more effective.
Keywords: EHRs; HIT; Healthcare; PHRs; RF; information technology